EVALUATION OF WEED CONTROL EFFICIENCY OF HERBICIDE RESISTANT TRANSGENIC COTTON - Abdul Qayyum Rao; Kamran Shehzad Bajwa; Allah Bakhsh; Muhammad Azam Ali; Adnan Iqbal; Ayesha Latif; Tayyab Husnain; Idress Ahmad Nasir; Ahmad Ali Shahid (Journal of Animal and Plant Sciences, 2023)
Weeds incur significant losses to the crop plants by not only competing with crops for water, nutrients, sunlight, and space but also harbour insects and diseases. The herbicide resistant cotton offers farming community an opportunity to combat weeds by providing flexibility of herbicide application whenever needed. In the present study, the herbicide resistant cotton was evaluated to unravel the glyphosate dose response at different time intervals. Glyphosate was applied on advance transgenic cotton line VH-289 at the time intervals of 20, 25, 30 and 40 days after germination and was compared with manual weeding of its conventional non-transgenic counterpart as control. The weed control efficacy, types, mortality, and population of nineteen different weeds were calculated with reference to the time and dose of glyphosate spray [600 mL.acre -1 (242 mL.ha-1), 800 mL.acre -1 (324 mL.ha-1), 1000 mL.acre -1 (305 mL.ha-1), 1200 mL.acre -1 (486 mL.ha-1), 1400 mL.acre -1 (566 mL.ha-1), 1600 mL.acre -1 (647 mL.ha-1), 1800 mL.acre -1 (728 mL.ha-1) and 2000 mL.acre -1 (809 mL.ha-1)] and its impact on yield. The yield and contributing characters like boll weight and cotton yield were higher in lines where glyphosate was applied at 20 and 30 days after germination compared to other treatment (manually hoed). Importantly, weeds control efficiency was recorded up to 98% at a dose concentration of 1800 mL.acre -1 and 2000 mL.acre -1 after 15-30 days after glyphosate application (DAS). The average number of bolls per plant in glyphosate resistant line was recorded higher compared to non-transgenic manually hoed control. This study highlights that spraying 1800 and 2000 mL.acre -1 glyphosate can help to eradicate weeds in field at less cost and good yield return. The results can be helpful for the cotton farmers regarding the proper concentration of glyphosate and its time of application.
Keywords: Herbicides; transgenic cotton; weed control efficacy; crop yield